Stress and Incivility among Indonesian Undergraduate Nursing Students: A Multivariate Analysis - Nelwati Nelwati; Feri Fernandes; Elvina Dwita; Rayung Ade Pratiwi (Fakultas Ilmu-ilmu Kesehatan, 2026)
Nursing faculty and students consider incivility as moderate to serious problem in nursing education programs. The primary cause of incivility among nursing faculties is stress. Indonesian undergraduate nursing students experience moderate to severe stress throughout the program. This study aimed to examine the effect of stress on incivility among Indonesian undergraduate nursing students and to identify the most significant factors predicting incivility in nursing education. A quantitative, cross-sectional study was conducted involving 220 Indonesian undergraduate nursing students from a public university in Indonesia that selected using convenience sampling. The instruments employed were the Student Nurse Stress Index and the Incivility in Nursing Education-Revised Scale. Ethical approval was granted from the relevant faculty. Descriptive statistics were used to analyze data, and multivariate analysis employing Structural Equation Modeling-Partial Least Squares (SEM-PLS) was conducted to determine the most significant predictor of incivility. The mean stress score was 67.18, indicating moderate stress, while the mean incivility score y was 46.50, which means high incivility. Age and academic year were negatively associated with incivility in nursing education, with p-values of 0.041 and 0.004, respectively. The clinical concern domain of stress was the most significant predictor of incivility among Indonesian undergraduate nursing students (p=0.000). It is expected that Indonesian undergraduate nursing students will effectively manage stress to control that incivility behavior and prevent negative impacts on themselves and their nursing education institutions. Seeking social support and utilizing campus resources can help alleviate difficulties with class materials, reducing feelings of fear related to failing exams and courses